Excel maths early skills book 10: multiply and divide - Dunbar, Bev (Oxford University Press Karachi, 2006)
"Excel Maths Early Skills Book 10: Multiply and Divide" introduces young learners to the concepts of multiplication and division through clear explanations and interactive exercises. It emphasizes developing a strong understanding of these operations, using visuals and practical examples to build confidence in early arithmetic skills.